Tejiendo lealtades en Charcas. El segundo juez de visita y composición de tierras en la trama de la dádiva virreinal, 1594-1600 - Jurado, M. Carolina (2017)
The economy of favor was an essential mechanism in the construction of monarchical and colonial power, encouraging the loyalty of subjects and a more effective control of the territory. Through an analysis of the residencia of don Pedro Osores de Ulloa, this article aims to examine the role of Charcas’s second visita and land composition judge in the exercise of colonial favor. The research suggests that land and the assignment of its property, mediated by Osores de Ulloa, formed the basis of loyalty and patronage relationships that strengthened viceregal power in Charcas and articulated different layers of power.